Optical method for identification and quantification of full-field stress distributions and evolution in assembled lining structures based on additively printed models and phase-shifting methods. (January 2022) - Ju, Yang; Wan, Changbing; Fu, Guoming; Mao, Lingtao; Chiang, Fu-pen
Highlights: Plane-stress-model-based photoelastic testing method was developed. Transparent assembled lining models were fabricated using 3D printing techniques. Continuous stress distributions in lining structures were revealed and quantified. Proposed method is effective for quantifying full-field stress distributions. Abstract: The accurate knowledge and characterization of the full-field stress distributions and evolution in assembled lining structures underlie the design, construction, and maintenance of tunnel linings. However, it is challenging for traditional field monitoring and laboratory experiments to identify directly and quantify accurately such distributions and evolution. Numerical simulations, as alternative solutions, are limited, as their results are significantly dependent on the accuracy of mechanical parameters, constitutive laws, failure criteria, mesh optimization, and boundary conditions, which are difficult to determine experimentally. In this study, a plane-stress-model-based photoelastic testing method was developed for the direct observation and quantification of the full-field stress distribution and evolution in an assembled lining structure based on additive manufacturing or three-dimensional printing technology and phase shifting methods. Three-dimensional printing techniques and stress- sensitive photopolymers were employed to fabricate transparent assembled models based on the information of real lining structures. The model split-merge technique, phase-shifting method, and unwrapping algorithm were combined to determine the full-field distribution of the principal stress difference and shear stress within the assembled segments. The proposed method was verified based on a comparison of the calculated and measured fringe orders at different loading stages. The experimental results indicated that the largest stress concentration was around the joint that connected the adjacent Segment L1 and basic Segment B1, which formed the potential critical failure zone of the assembled structure. An approximate X-shaped shear band was also identified. Comparisons of the results verified that the boundary and contact conditions, which are difficult to simulate, can lead to significantly different simulation results with respect to the distribution and evolution of the principal stress difference and shear stress. This study shows that the proposed method can effectively and quantitatively characterize the full-field stress distributions and evolution within complex assembled lining structures.